A unified 2-D model for nanowire junctionless accumulation and inversion mode MOSFET in quasi-ballistic regime. (July 2022) - Baral, Kamalaksha; Singh, Prince Kumar; Kumar, Sanjay; Singh, Ashish Kumar; Jarwal, Deepak Kumar; Jit, Satyabrata
Highlights: The Model is applicable to both Inversion Mode MOSFET and JAM MOSFET for all regions of operation. The model is applicable to very short channel MOSFET (∼10 nm) where quasi ballistic transport mechanism is dominant. The model accurately supports channel doping from intrinsic level to the doping of 10 19 cm −3 . Abstract: A unified 2-D continuous potential model for cylindrical nanowire junctionless accumulation mode (JAM) MOSFET and conventional inversion mode (IM) MOSFET has been presented in this manuscript. The 2-D Poisson's equation in cylindrical coordinates is solved analytically with the help of the superposition principle and evanescent mode analysis of the Fourier-Bessel series is performed. Both free and depletion charges are considered in the 2-D Poisson's equation. The model thus derived is continuous across different operation regimes (depletion and accumulation/inversion) with respect to VGS . Further, a threshold voltage model is also derived from the potential model and an expression of drain-induced barrier lowering (DIBL) is formulated. The short channel drain current model is derived from the potential-based charge model and quasi-ballistic transport velocity model. Furthermore, models for transconductance ( gm ) and output conductance ( gd ) is also formulated from the drain current model. A 3-D TCAD tool from Cogenda TM has been used to numerically verify our proposed unified analytical model.